Clarence Brown : Hollywood's Forgotten Master - Young, Gwenda (Book collections on Project MUSE., 2018)
"Gwenda Young's "Clarence Brown: Hollywood's Forgotten Master" is an in-depth analysis of the life and films of Clarence Brown. After tracing Brown's lineage from hardworking parents and resilient grandparents, it presents his films in a way that captures and holds readers' attention. It approaches Brown the director from a unique perspective, deriving information from interviews, books, newspapers, and obituaries. Each film is described in detail, including how it was made, how the actors and crew felt about the piece, how the film influenced Brown's growth as a director, and how the film contributed to Hollywood and tied in to current issues of the day. The book discusses the political, racial, gender, and social attributes Clarence Brown saw in others and in himself across the span of five decades. Brown's place within the Golden Age of Hollywood and his collaborations with key stars are also examined"--